Evaluating the Potential of Marine Algae as Sustainable Ingredients in Poultry Feed - Hanan S. Al-Khalaifah; Afaf Y. Al-Nasser (Agriculture)
Algae are a complex source of crucial nutrients, including proteins, minerals, vitamins, and carbohydrates. The use of marine algae, specifically Sargassum species, Gracilaria species, and Spirulina species, as feed ingredients in poultry feed was examined in the current research. This study’s aims were to carry out lipid profiling, proximate analysis, and heavy metal toxicity testing, as well as to evaluate the presence of hazardous hydrocarbons in the algae and investigate the effect of the fatty acid profile of Sargassum species on broilers. The proximate analysis was conducted on the algae types containing considerable quantities of fats and proteins and a sizable quantity of omega-3 fatty acids. This research assessed the productive effectiveness of broilers with 2.5%, 6%, and 10% algal additions in their diet. Fatty acid profiling of Sargassum species was performed at 1% and 2% levels in the bursa, fat pads, heart, liver, spleen, thymus, thighs, and breast. The findings showed no significant differences in the development performance or feed utilization efficiency of broilers with 2.5%, 6%, and 10% algae supplementation in their diet. The results of fatty acid profiling showed changes in the heart, liver, and spleen at 1% and 2% supplementations levels. However, this research concludes that if algae partially replaces the imported feed proteins used in animal feed, then these can achieve maximum beneficial effects on poultry health and performance. Algae are sustainable, easy to produce, and cost-effective sources of nutrients and contain numerous bioactive compounds, which will contribute to sustainability and food safety.